Congenital Cytomegalovirus Infection Masquerading as Antenatal Ventriculomegaly With Intraventricular Hemorrhage in a Term Neonate. (January 2020) - Bhattacharya, Deepanjan; Anil Kumar, B. N.; Panigrahi, Inusha; Kaur, Anupriya
Intraventricular hemorrhage is an uncommon manifestation of congenital cytomegalovirus (CMV) infection and has been described in preterm neonates. We discuss a term neonate, who was referred because of intracranial hemorrhage and hydrocephalous detected in the antenatal ultrasound. She had cholestatic jaundice, hepatitis, and thrombocytopenia, with positive polymerase chain reaction for CMV. Neuroimaging revealed reduced sulcation, mildly enlarged ventricles, and multiple periventricular cysts, along with residual hemorrhage in occipital horn of left lateral ventricle. She was started on ganciclovir, following which there was improvement in platelet count, jaundice, as well as transaminase levels.